Penerapan Algoritma Vertical Bit Rotation (VBR) Dalam Penyimpanan File Online - Citra, Ebiet Nico (MEANS (Media Informasi Analisa dan Sistem), 2018)
Many facilities offered, but in terms of security, there is no absolute security. One way to secure files is to encrypt the file with cryptographic algorithms, and in this study Vertical Bit Rotation (VBR) cryptographic algorithms will be used as cryptographic algorithms that are used to increase the level of security in terms of storing files online. This algorithm is as simple as the classic cryptographic algorithm but with the security as strong as modern cryptographic algorithms. For further development, the paper will include stages of encryption in more detail, use of keys, examples of encryption codes, and examples of usage